Pattern of Maxillofacial Injuries in Pediatric Patients – A Hospital Based Retrospective Study - Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Tripathi, Shashank; Pahari, Bikash; Shubham, Snigdha; Gautam, Narayan (Birat Journal of Health Sciences, 2020)
Introduction: Maxillofacial injuries are less frequent in children than adults and are more often minimally displaced. Literature reveals that the incidence of maxillofacial injuries accounts for 1% - 14.7% in children below age 16 years. There is lack of information on epidemiological data for pediatric maxillofacial injury from Nepal. Objectives: The objective of the study is to determine the pattern of maxillofacial injuries in the pediatric population who had been treated in one of the tertiary level hospitals in western Nepal. Methodology: Among 303 cases of maxillofacial trauma registered between March 2017 to February 2019 at UCMS College of Dental Surgery, Bhairahawa, Rupandehi, Nepal; 57 cases of pediatric maxillofacial injuries that were admitted and received treatment were enrolled in the study. Parameters recorded were demographic data, mode of injury, the pattern of maxillofacial injuries and treatment provided. Results: Majority of patients were males (66.67%) among which 51% were adolescents (12-16 years). The mode of injury was road traffic accidents (77.2%) in most cases. Mandibular fractures were commonly seen in which parasymphysis region (40%) was common anatomic site. Most of the injured patients (45.6%) were managed with open reduction and internal fixation. Post-operative results were uneventful. Conclusion: The road traffic accident was the predominant mode for injury. Mandible is one of the most commonly involved bones to get a fracture. Good traffic sense needs to be imbibed and developed by the government as well as the public to prevent road traffic accidents. In addition, children need to carry out their outdoor activities under adult supervision.